2016
DOI: 10.1177/1558944716660555jn
|View full text |Cite
|
Sign up to set email alerts
|

Carpal Tunnel Syndrome

Abstract: Objective: An emerging body of evidence suggests an association between pain and altered neural representations of the body. The integrity of these neural representations can be assessed with a timed motor imagery task such as the left/ right judgment task (LRJT). The purpose of this investigation was to systematically evaluate the literature and use meta-analytical methods to establish whether performance of the LRJT is impaired in people with upper limb pain. Materials and Methods: The literature was systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This is consistent with a recent pilot study that found that a physical therapy approach focusing on the entire nerve pathway from its origin (cervical) through neural mobilization and cervical segmental stabilization techniques resulted in significant reductions in DASH scores when compared to a control group that received a traditional therapeutic exercise program. ( 44 ) Large effect size in DASH scores improvement six months after cervical manual therapy plus conventional physical therapy, that was greater than the minimally clinically important change (MCIC), ( 45 ) indicates that, with passage of time, DASH scores of functionality further improved. It follows that physiotherapists should expect significantly greater DASH score improvement beyond the immediately-after-end of treatment, at least six months later, in patients with mild to moderate CTS.…”
Section: Dashmentioning
confidence: 99%
“…This is consistent with a recent pilot study that found that a physical therapy approach focusing on the entire nerve pathway from its origin (cervical) through neural mobilization and cervical segmental stabilization techniques resulted in significant reductions in DASH scores when compared to a control group that received a traditional therapeutic exercise program. ( 44 ) Large effect size in DASH scores improvement six months after cervical manual therapy plus conventional physical therapy, that was greater than the minimally clinically important change (MCIC), ( 45 ) indicates that, with passage of time, DASH scores of functionality further improved. It follows that physiotherapists should expect significantly greater DASH score improvement beyond the immediately-after-end of treatment, at least six months later, in patients with mild to moderate CTS.…”
Section: Dashmentioning
confidence: 99%